A GENRE-BASED ANALYSIS OF VARIATION IN THE SOCIAL SCIENCE AND MECHANICAL ENGINEERING ABSTRACTS IN ENGLISH AND SERBIAN - Maglov, Sanja (PALIMPSEST / ПАЛИМПСЕСТ, 2018)
The use of the English language in academic communication has been increasing in the last decades. Such increased use has effect on discourse and rhetorical properties of genres across languages or sometimes English even replaces national languages completely. The aim of this article is to study the presence and potential influence of genre-based conventions specific to English on the rhetorical organization in Serbian by comparing social science and mechanical engineering abstracts in the two languages. Besides the overall move frequency, the total number of moves in each abstract, as well as move repetition and move embedding are analyzed. The analysis showed that linguistic, cultural and disciplinary factors have influence on academic discourse in both languages. In particular, there is more variation between the two social science groups of abstracts. On the other hand, the engineering abstracts are more similar, although the ones in Serbian have a simpler macrostructure, fewer moves and fewer meta-discourse and promotional elements. The awareness of such differences can help Serbian authors when they want to publish in English and become members of the global academic community.